2013
DOI: 10.1093/molbev/mst271
|View full text |Cite
|
Sign up to set email alerts
|

Ignoring Heterozygous Sites Biases Phylogenomic Estimates of Divergence Times: Implications for the Evolutionary History of Microtus Voles

Abstract: Phylogenetic reconstruction of the evolutionary history of closely related organisms may be difficult because of the presence of unsorted lineages and of a relatively high proportion of heterozygous sites that are usually not handled well by phylogenetic programs. Genomic data may provide enough fixed polymorphisms to resolve phylogenetic trees, but the diploid nature of sequence data remains analytically challenging. Here, we performed a phylogenomic reconstruction of the evolutionary history of the common vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 82 publications
4
108
2
1
Order By: Relevance
“…Similar patterns were found in humans were genetic data also mirror geography in Europe [84]. This high resolution indicates the large information content present in this AFLP data set and is further supported by a very similar PCA-based clustering of populations inferred by 6,807 polymorphic SNPs (see Figure S2 in [60]), which were used to resolved the four evolutionary lineages present in Europe [43].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar patterns were found in humans were genetic data also mirror geography in Europe [84]. This high resolution indicates the large information content present in this AFLP data set and is further supported by a very similar PCA-based clustering of populations inferred by 6,807 polymorphic SNPs (see Figure S2 in [60]), which were used to resolved the four evolutionary lineages present in Europe [43].…”
Section: Discussionsupporting
confidence: 77%
“…[91], [95], [96]). An alternative strategy would be the investigation of candidate loci for selection by direct high-throughput sequencing of AFLP fragments [60], [97], which could be useful to further characterize candidate regions and genes linked with AFLP markers in this non-model organism.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, simulation studies have shown that the concatenation procedure can provide high statistical support for an incorrect species tree, because lineage sorting processes are not modeled (Kubatko and Degnan 2007). Finally, branch length estimates are affected when heterozygous sites are excluded from phylogenetic analyses (Lischer et al 2014), which was common practice in phylogenetic analyses of concatenated autosomal data. Conceptual advances and recently developed coalescence-based multilocus species tree approaches now provide a means to infer overall phylogenetic relationships (species trees), against which individual gene trees can be contrasted to identify the underlying evolutionary processes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we employed the repeated random haplotype sampling (RRHS) strategy 62 when phase information was required. RRHS randomly assigns one of two possible genotypes at heterozygous sites.…”
Section: Methodsmentioning
confidence: 99%